Optimized design of a non-isopeak-ring endovascular stent graft for thoracic aortic aneurysm. - Zhou, Yu; Song, Chengli; Zhang, Ailing; Yan, Shiju (Minimally Invasive Therapy & Allied Technologies, 2025)
Background: To optimize the design of the stent graft (SG) with a non-isopeak-ring, this study investigates the radial support and bending flexibility properties of SGs with different spacing, number of peaks, and peak heights. Methods: Numerical simulation and physical experiments were used to compare the mechanical properties of isopeak-ring SGs and non-isopeak-ring SGs. Results: Greater spacing of stent rings can provide greater bending flexibility; fewer peaks in the stent ring result in more radial support and less spring-back force. The SG design featuring a gradient of five wave peaks and a minimum stent ring spacing of 5 mm has the best flexibility. The relationship in terms of radial support force magnitude is as follows: isopeak-ring with heights of 13 mm > combination > gradient > isopeak-ring with heights of 16 mm. Additionally, the smaller the peak height, the greater its radial support. Conclusions: It is found that the gradient SG with five peaks not only provides sufficient radial support but also demonstrates superior flexibility compared to other types of SGs.